2021
DOI: 10.3897/asp.79.e66966
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of the enigmatic longhorned beetle Vesperoctenus flohri Bates (Vesperidae) and a first description of its female internal structures

Abstract: Taxonomic placement of the enigmatic monotypic Mexican longhorned beetle genus Vesperoctenus Bates is examined through inclusion in and reanalysis of the dataset of Haddad et al. (2018, Systematic Entomology 43: 68–89). We describe and discuss the phylogenetic significance of the internal structures of a recently collected V. flohri female from the Sierra de la Laguna mountain range in Mexico, the same specimen from which phylogenomic data was generated. Our phylogenomic analyses (469 genes) recovered Vesperoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…A recent molecular phylogeny of Chrysomeloidea supported the recognition of six to eight subfamilies within Cerambycidae, with Oxypeltidae, Disteniidae and Vesperidae as distinct families (Haddad et al, 2018). Haddad et al (2021) expanded this dataset to include the enigmatic taxon Vesperoctenus Bates (Vesperidae: Vesperoctenini Vives) and recovered a similar result. The molecular datasets used in these studies, comprised of anchored hybrid enrichment (AHE) data (Lemmon et al, 2012) from over 500 nuclear loci, are substantially larger than all previous studies and include a more comprehensive sample of higher taxa.…”
Section: Introductionmentioning
confidence: 76%
“…A recent molecular phylogeny of Chrysomeloidea supported the recognition of six to eight subfamilies within Cerambycidae, with Oxypeltidae, Disteniidae and Vesperidae as distinct families (Haddad et al, 2018). Haddad et al (2021) expanded this dataset to include the enigmatic taxon Vesperoctenus Bates (Vesperidae: Vesperoctenini Vives) and recovered a similar result. The molecular datasets used in these studies, comprised of anchored hybrid enrichment (AHE) data (Lemmon et al, 2012) from over 500 nuclear loci, are substantially larger than all previous studies and include a more comprehensive sample of higher taxa.…”
Section: Introductionmentioning
confidence: 76%
“…Horn (1894: p. 326) mentioned that "San Francisquito" is in the Cape province, which is located more than 800 km to the south in the present-day state of Baja California Sur; hence, the state of Baja California is excluded from the distribution of V. flohri. In the same work by Haddad et al (2021), a locality mentioned by Hovore (1988) ("Santa Victoria, La Laguna, 23.09320, −109.95846") was georeferenced at 500 m; however, in the original work by Hovore (1988) it appeared at 1,950 m.…”
Section: Resultsmentioning
confidence: 94%
“…Geographical records for V. flohri were obtained from the following institutional collections: CNIN-Colección Nacional de Insectos, UNAM, Mexico (S. Zaragoza); IEXA-Colección Entomológica del Instituto de Ecología, AC, Mexico (V. Vega Badillo); EMEC-Essig Museum of Entomology, University of California, Berkeley, CA, USA (P. T. Oboyski). Records were also obtained from Naturalista (2022) and Haddad et al (2021); however, only those that were certain were included. These efforts yielded 16 total records of occurrence (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insect ovary is the key organ in insect population mating and oviposition, and the numbers of female individuals and ovarian eggs determine whether the insect population can persist in nature for a long time (Bueno et al, 2020; Koji et al, 2020; Amano and Nomura, 2021; Gotoh and Sasaki, 2021). A study found that the morphological characteristics of the internal reproductive organs of females, especially ovaries, change dramatically in a short time from emergence to death for most insects (Chiang, 2020; Haddad et al, 2021; Ji et al, 2021). Because individual pest population ovary metabolism is more active, females can lay a large number of eggs, and the life span of some pest populations can be up to 2-6 months.…”
Section: Introductionmentioning
confidence: 99%